The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1111/j.1728-4465.2002.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Large‐scale Transitions to Quality of Care: An Idea Whose Time Has Come

Abstract: In the field of reproductive health, investigation of the transfer of knowledge gained from demonstration and pilot projects to large public-sector programs typically has not been considered a relevant domain for research or other investigation. This article draws on a range of research in the social sciences and presents two frameworks for understanding the critical attributes of successful expansion of small-scale innovations. Seven key lessons are developed using examples from family planning where scaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…We have shown that a supported cascade training system can successfully train several teachers through existing local government systems. Other studies have identified national level endorsement or "policy windows" as important should a large-scale intervention be achieved and sustained [27][28][29]. Our research suggests that national policies relating to more frequent supervision, inclusion of behavioral and skills topics in the national examinations, and pre-service training could significantly strengthen quality and fidelity of ASRH interventions.…”
Section: Discussionmentioning
confidence: 55%
“…We have shown that a supported cascade training system can successfully train several teachers through existing local government systems. Other studies have identified national level endorsement or "policy windows" as important should a large-scale intervention be achieved and sustained [27][28][29]. Our research suggests that national policies relating to more frequent supervision, inclusion of behavioral and skills topics in the national examinations, and pre-service training could significantly strengthen quality and fidelity of ASRH interventions.…”
Section: Discussionmentioning
confidence: 55%
“…However, little is known about how best to implement such programmes on a scale great enough to significantly impact on adolescent sexual and reproductive health (ASRH) on this continent. Programme scale-up is complex: it is not simply a large-scale replication of a 'blue print' but the product of an interaction between an ideal intervention and the cultures, priorities and capacities of the structures through which it is scaled up [3-6]. Simmons et al have developed models of scale-up and a series of recommendations based on an interrogation of public health case studies against diffusion of innovation and organizational development theories.…”
Section: Introductionmentioning
confidence: 99%
“…Simmons et al have developed models of scale-up and a series of recommendations based on an interrogation of public health case studies against diffusion of innovation and organizational development theories. These suggest that, in order to be sustainable, interventions must be scaled up through existing systems [3,6] and are most likely to succeed if intervention design is tailored to, and involves the structures through which scale-up is intended [6]. An integrated version of their model is presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Simmons and colleagues have identified seven elements of successful expansion programs, including allowing for adaptation and incremental change, working through the political process by adopting a highly pragmatic management style and engaging the support of one or more policymakers who are open to change. 8 The Egyptian postabortion care experience is an example of how these elements contributed to the successful expansion of a small-scale activity into a national program, and the lessons learned are applicable to other settings. …”
mentioning
confidence: 99%